A ideia do museu : Fernando Távora, Álvaro Siza Vieira e Eduardo Souto de Moura - Freitas, Sílvia Raquel Lopes, 1989- (2014)
Dissertação de mestrado integrado em Arquitectura, Universidade Lusíada de Lisboa, 2014